Back to oil: Indonesia economic growth after Asian financial crisis - Heru Iswahyudi (Universitas Islam Indonesia, 2016)
This paper examines the growth experience of Indonesia in the years before and after the Asian financial crisis. Particular attention is paid to the relationship between economic growth and petroleum sector’s total factor productivity (TFP). It finds the possibility that post-crisis Indonesian economic growth has ‘recoupled’ with petroleum sector’s TFP – fluctuations in petroleum TFP is directly correlated with fluctuations in economic growth. Further, although keeping Indonesia’s petroleum sector open to fair competition should be the prime policy, the fact regarding resource nationalism might need to be taken into account in designing the policy to develop the productivity of Indonesia’s petroleum sector.